Exploring the experiences related to sexuality and intimacy of women treated for cervical cancer at Windhoek Central Hospital - Rugara, Mellody (Stellenbosch : Stellenbosch University, 2026)
Thesis (MHumanRehabSt)--Stellenbosch University, 2025.